EVALUATION OF STABILITY PARAMETERS FOR COMPOSTING OF SOLID WASTE PRODUCTION AND CHARACTERIZATION OF COMPOST - Hussein N. Abd; Hussein M. Flayeh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The compost product enhances soil quality, lowers erosion, and aids in the reduction of plant diseases without having a negative influence on the environment. The possibility for compost recovery from organic waste, fruit waste, agricultural residues, domestic garbage, and animal manure was examined in this study. These wastes are composted in a five-week aerobic -pile composting process. The temperature, pH, moisture, electrical conductivity, carbon to nitrogen ratio (C/N-ratio), nitrification index (NH4-N/NO3-N), and NPK (Nitrogen, phosphorous, and potassium( value of the finished compost were all measured both during and after the composting process. These physio-chemical characteristics and parameters that affected the composting process included temp., pH, moisture, and electrical conductivity.The results revealed long - term negative impacts characteristics for moisture content, electrical conductivity (reached 1.5-2.34 dS/cm), total organic carbon, C/N ratio (reached 17.3-13.5), and increase in nitrogen content per unit material for the more, with composting time the nitrification index NH4+/NO3-ratio decreased by less than 0.5, as with overall increasing PH profiles. pH-value varying from (4–8) during the composting process, and GI values greater than 90 at the conclusion of the composting period. The bio-pile R3 was found to be the most helpful for composting, according to the data. It maintained the highest temperature for the longest period of time (52–60 oC), then gradually dropped to ambient temperature, which is seen as a sign that the composting process had ended and the finished compost was a mature and stable product.